Family Resilience Strategies among Dual-Career Faculty Couples at Indonesian Islamic Universities: An Analysis Based on Euis Sunarti’s Family Resilience Theory - Silviani, Endiana; Mohamad Khafid Maulana (KALOSARA: Family Law Review, 2026)
The professional demands of the Tri Dharma of Higher Education often lead to role conflict and burnout among married couples who both work as university lecturers. This study aims to explain the family resilience strategies of dual-career faculty couples at State Islamic Religious Universities (PTKIN) using Euis Sunarti’s Family Resilience Theory. The research method employed is qualitative field research with a juridical-empirical approach. The research subjects consisted of two couples of tenured lecturers selected based on specific criteria of high workloads and having school-aged children. Data were collected through separate in-depth interviews and documentation of lecturers’ workload reports, then analyzed using an interactive model (reduction, presentation, and drawing conclusions) and tested through data triangulation. The research results indicate that family resilience strategies are manifested through three aspects of well-being: (1) physical well-being is achieved through transparent management of dual-income and the establishment of an emergency fund; (2) psychological well-being is managed through strict emotional regulation that separates academic workload from domestic responsibilities; and (3) social well-being is reflected in flexible negotiation of domestic roles (“whoever has time does the work”) and the utilization of extended family support systems. The implications of this research confirm that the resilience of academic families is not automatically created by economic or educational factors, but rather through a dynamic process of adaptation and negotiation.  Concretely, this study contributes to the field of family sociology and higher education management by providing a specialized empirical model of domestic resilience within Islamic academic institutions, which can serve as a strategic baseline for developing family-friendly university policies. Keywords: Dual-Career; Euis Sunarti; Faculty Couples; Family Resilience; Strategies.